PELATIHAN MANAJEMEN EVEN UNTUK MENINGKATKAN BRANDING PRODUK UMKM DESA DUWET KECAMATAN TUMPANG KABUPATEN MALANG - Evi Suwarni; Tiara Estu Amanda; Prima Beauty Kartikasari; Alvin Nouval; Cahyo Ramadhan Pratama (Jurnal Pengabdian kepada Masyarakat, 2025)
The purpose of this community service program is to enhance the event management skills of the SMEs (UMKM) in Desa Duwet, Kecamatan Tumpang, Kabupaten Malang. The approach used includes a series of training and mentoring sessions focused on improving event planning, budgeting, marketing, communication, community engagement, crisis management, and sustainability. The goal is to empower the local community to manage events effectively and sustainably such as bazaars and exhibitions. The result of this program was an increase in the SMEs' capacity to independently manage local events, which in turn boosted local economic activity and promoted product branding.